(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article describes the problems of determining the effectiveness of employees in the service sector and shows the shortcomings of existing indicators. Also, new indicators are proposed and analysed that determine the efficiency of industry workers, and conclusions are drawn on the example of service sector networks.